Proteomic Profiling of a Layered Tissue Reveals Unique Glycolytic Specializations of Photoreceptor Cells - Reidel, Boris (The American Society for Biochemistry and Molecular Biology, 2011)
The retina is a highly ordered tissue whose outermost layers are formed by subcellular compartments of photoreceptors generating light-evoked electrical responses. We studied protein distributions among individual photoreceptor compartments by separating the entire photoreceptor layer of a flat-mounted frozen retina into a series of thin tangential cryosections and analyzing protein compositions of each section by label-free quantitative mass spectrometry. Based on 5038 confidently identified peptides assigned to 896 protein database entries, we generated a quantitative proteomic database (a “map”) correlating the distribution profiles of identified proteins with the profiles of marker proteins representing individual compartments of photoreceptors and adjacent cells. We evaluated the applicability of several common peptide-to-protein quantification algorithms in the context of our database and found that the highest reliability was obtained by summing the intensities of all peptides representing a given protein, using at least the 5–6 most intense peptides when applicable. We used this proteome map to investigate the distribution of glycolytic enzymes, critical in fulfilling the extremely high metabolic demands of photoreceptor cells, and obtained two major findings. First, unlike the majority of neurons rich in hexokinase I, but similar to other highly metabolically active cells, photoreceptors express hexokinase II. Hexokinase II has a very high catalytic activity when associated with mitochondria, and indeed we found it colocalized with mitochondria in photoreceptors. Second, photoreceptors contain very little triosephosphate isomerase, an enzyme converting dihydroxyacetone phosphate into glyceraldehyde-3-phosphate. This may serve as a functional adaptation because dihydroxyacetone phosphate is a major precursor in phospholipid biosynthesis, a process particularly active in photoreceptors because of the constant renewal of their light-sensitive membrane disc stacks. Overall, our approach for proteomic profiling of very small tissue amounts at a resolution of a few microns, combining cryosectioning and liquid chromatography-tandem MS, can be applied for quantitative investigation of proteomes where spatial resolution is paramount.